Book Review: Barnett, M.N., editor. 2017: Paternalism beyond Borders. (October 2018) - Macias-Arteaga, Jazmin
Barnett, M.N., editor. 2017: Paternalism beyond Borders . Cambridge: Cambridge University Press. x + 353 pp. £64.99. ISBN: 978 1 107 17690 4 (hardback). £22.99. ISBN: 978 1 316 62571 2 (paperback). £14.04. ISBN: 1107176905 (e-book).